Development and validation of mass reduction prediction model during torrefaction using biomass chemical composition analysis - Sunyong Park; Kyeong Sik Kang; Kwang Cheol Oh; Seok Jun Kim; Paudel Padam Prasad; Seon Yeop Kim; Ha Eun Kim; Jae Youl Shin; DaeHyun Kim (PLoS ONE, 2025)
Thermochemical processes employ heat to transform biomass into energy. In these processes, heat supply and biomass type can affect the products, therefore understanding them is critical. Confirming these changes directly requires time and resources. Several hypotheses have been proposed to explain these changes. So, the purpose of this work was to investigate mass loss during thermochemical reactions utilising available kinetic parameters. This study comprised previously pyrolysed herbal agricultural biomass (soybean pod, corncob), woody agricultural biomass (pepper stem, grape pruning branch), and forestry biomass (wood pellet, bamboo). Temperature fluctuations were studied using a 1D temperature prediction model and evaluated using kinetic parameters. The findings anticipated using prior research’ kinetic parameters differed by up to 20% from the experimental results. As a result, some of the kinetic parameters were adjusted. The prediction model with the changed parameters outperformed the prior results, with an RMSE of 2.0607 for wood pellets and 5.9754 for soybean pods. The results obtained using grape pruning branches, bamboo, and corncobs confirmed the mass reduction predicted by prior studies. This study revealed the capacity to estimate mass loss without using thermogravimetric measurements, and future predictions should include a broader spectrum of biomass materials.